Pengaruh Kompetensi Aparat Dan Inovasi Layanan Terhadap Kualitas Pelayanan Publik Pada Kantor Desa Dengeng-Dengeng Kecamatan Pitu Riase Kabupaten Sidrap - Nurhidayatul Aini; Edi Jusriadi; Sitti Nurbaya (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine and analyze the influence of staff competence and service innovation on the quality of public services at the Village Office of Dengeng-dengeng, Pitu Riase District, Sidenreng Rappang Regency (Sidrap). This research is a quantitative study using data collection methods through observation and the distribution of questionnaires to the community as respondents. The sample was determined using the Slovin formula. The data sources include both primary and secondary data. The data analysis technique employed is multiple linear regression analysis with the help of the Statistical Package for the Social Sciences (SPSS). The results indicate that staff competence and service innovation have a positive and significant effect on the quality of public services. This means that the higher the level of staff competence and the better the implementation of service innovations, the better the quality of public services provided to the community.